Understanding the Effect of Green Brand Activism on Purchasing İntention of Millennials in India - Rahul Mukherjee (International Journal of Advanced Science and Technology, 2020)
Millennials from all over the world are getting increasingly aware about the environment and the hazards it is facing. Protests can be seen all over the world. People from Generation Y are actively vocal of their concern. Brands have been observing this rise in consciousness among the millennials. Some of these brands are trying to communicate their campaigns and advertisements to the millennials focusing on sustainability and eco-friendliness. A similar trend has been observed in India. The main aim of this research has been to try to understand the shift in purchasing intention of Indian millennials towards a brand on being exposed to advertisements which are pro-environment.  Online survey has been used to reach out to 268 millennials out of which 103 submissions have been received and used. Cluster analysis has been used to understand the different segments in millennials based on their exposure. The study has taken into account factors such as sex of the individual, environmental knowledge and concern, green brand activism perception and green campaign/advertising undertaken by the brand. Cronbach’s alpha test has been conducted to check if the constructs are coherent to our research. The study will help brands to understand whether their campaigns or advertisements happen to sway the intention of millennials in India to buy products of their brand